Study of Geo filtration Processes of a Water Intake Structure Based on A Set of Mathematical Modeling and Software - J.H.Jumanov; R.A.Yusupov; A.F.Rasulov (Genius Publishing Group, 2023)
In the article, the problem of modeling geofiltration processes in the water intake area, constructing numerical solution algorithms and providing the population with highquality drinking water based on software has been studied and investigated. The determination of changes in the level of river water, water resources, taking into account changes in hydrogeological conditions, groundwater and surface water, was carried out using a large number of effective computational experiments based on the created software, issues of increasing reserves and preventing depletion of groundwater deposits were discussed.
Keywords: Groundwater; geo filtration model; software package